EGF receptor family: targets for cancer therapeutics - Burgess, Tony (Henry Stewart Talks, 2007)
The association of the Epidermal Growth Factor Receptor (EGFR) with the tumorigenic state, The four related members of the EGFR family (EGFR, erbB2, erbB3 and erbB4), Signaling of the activated receptors as either homo- or heteromeric oligomers, Activation of the EGFR by excess ligand stimulation, receptor over-expression and/or mutation in many carcinomas, Utility of antibodies and receptor kinase inhibitors which interfere with signaling from the EGFR family as agents in cancer therapy, The three-dimensional structures for the extracellular domains of EGFR, erbB2, erbB3 and erbB4 and the discovery that EGFR, erbB3 and erbB4 undergo major conformational transitions when interacting with their ligands, Development of antibodies (mab806) which reduce tumor formation from cells expressing either truncated D2-7 EGFR or over-expressed EGFR by binding to the receptor in a region normally masked by the dimerization of the EGFR extracellular domain, Use of EGFR antagonists or inhibitors to increase tumor killing by cytotoxic anti-cancer drugs and/or radiation, Improvement of tumor killing by combining EGFR antagonists and EGFR kinase inhibitors
Archived at 2021/02/25